Патентные исследования как фактор интенсификации формирования интеллектуальной собственности - Balchiunene N. I. (Инновационные технологии в науке и образовании, 2015)
an example of Petrozavodsk State University shows that the patent research, combined with the scientific substantiation of parameters and modes of operation of machinery and equipment are the most important factor in the formation of patentable intellectual property.
Keywords: интеллектуальная собственность; научное обоснование; патентные исследования; intellectual property; scientific substantiation; patent research